RESEMBLANCE OF INDIRECTNESS IN POLITENESS OF EFL LEARNERS’ REQUEST REALIZATIONS - Syahri, Indawan (Universitas Pendidikan Indonesia, 2013)
Abstract: Politeness principles are universally utilized by the speakers of any language when realizing various speech acts. However, the speakers of particular languages relatively apply politeness due to the cultural norms embedded. The present study attempts to delineate how the Indonesian learners of English (ILE) apply the politeness principles in request realizations. Specifically it devotes to the types of politeness strategies applied and resemblance of the indirectness in politeness strategies in requesting acts. The FTAs and indirectness are the theoretical bases used to trace the typologies of both politeness and request strategies. The data werere collected by means of certain elicitation techniques, i.e. DCTs and Role-plays. The analyses werere done through three stages; determining request strategies, politeness strategies, and resemblance of indirectness in politeness. The results show that the indirectness generally is parallel to politeness. Besides, some pragmatic transfers are found in terms of applying native-culture norms in realizing target speech acts.